Method, structure, and development in al-Farabi's cosmology - Janos, Damien. (Islamic Philosophy, Theology and Science. Texts and Studies, 2012)
This study-the first monograph devoted exclusively to al-Fārābī's cosmology-provides a new interpretation of this thinker's philosophical development through an analysis of the Greek and Arabic sources and a contextualization of his life and thought in the cultural and intellectual milieu of his time. It discusses key cosmological and metaphysical concepts articulated in his works, with a special focus on celestial causation, intellection, and motion. This book also examines al-Fārābī's cosmological method and particularly the connection between astronomy, physics, and metaphysics. The result is a reassessment of al-Fārābī's cosmology vis-à-vis late-antique Greek philosophical trends and a clearer understanding of how it creatively adapted and transformed this legacy to establish a new cosmological paradigm in Arabic thought.